Analisis Penerapan Software Accurate dalam Meningkatkan Efektivitas Sistem Informasi Akuntansi pada Perusahaan Konstruksi - Rizqi Amanda Azzahra; Mumpuni Wahyudiarti Sitoresmi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Developments in information technology have encouraged businesses to utilize software-based accounting information systems to improve efficiency and accuracy in managing financial data. One of the accounting applications widely used by companies in Indonesia is Accurate. This study aims to evaluate how the implementation of Accurate software can enhance the effectiveness of accounting information systems in the construction sector. The methodology employed in this research is a qualitative approach using a case study. Data were collected through several techniques, including observation, interviews, and document analysis related to the company’s financial data management processes. The findings indicate that the use of Accurate software is able to improve the effectiveness of accounting information systems through faster, more accurate, and integrated transaction recording processes. In addition, the utilization of Accurate software enables more systematic financial data processing and financial reporting, thereby reducing recording errors and increasing work efficiency in the company’s finance department. In other words, the implementation of Accurate software has the potential to assist construction companies in improving the quality of financial information management and supporting more accurate managerial decision-making.